Fluoride Ionic Liquids in Salts of Ethylmethylimidazolium and Substituted Cyclopropenium Cation Families - Curnow, Owen J.; MacFarlane, Douglas R.; Walst, Kelvin J. (Frontiers in Chemistry, 2018)
A series of solvent-stabilized ionic liquid fluorides were prepared, [EMIM]F.nCH3COOH n = 1.0, 1.6, 2.1, 2.4 and 3.2, either via exchange from the chloride salt using KF or AgF, or by neutralization of the hydroxide salt using HF. Azeotrope drying was used to remove water. Their viscosity, conductivity and density properties were determined. A diethanol solvate of the triaminocyclopropenium salt [C3(NPr2)3]F was found to be stable and its viscosity, conductivity and density properties were also determined. The monoethanol solvate, however, was found to be unstable with trace water present. Intramolecular stabilization of fluoride was achieved by using OH functionalized cations: [C3(NEt2)2N(CH2CH2OH)2]F, [C3(N(CH2CH2OH)2)3]F, and [Me3NCH2CH2OH]F.H2O, The first of these is an ionic liquid at ambient temperature and has a TGA mass loss onset at 175 °C, indicating a useful range of liquid state stability.